Study of attitudes towards values among High School Students - N, Ramalingam; G, Palanivelu (International Research Journal of Tamil, 2021)
Field research was used to find a attitude towards value among high school students. In Tiruvallur district, 250 high school students were selected as study samples in simple event sampling. The data was designed and the data was designed by the Sublime Attitude Scale Investigator to collect research data. The data collected was tested using analyses at the point of average, deplanation, t-test, etc. As a result of the study, high school students have a significant difference in their gender, language of instruction and school location. To bridge these differences, teachers should first be trained in workplaces to teach values in conjunction with the subject. In order to encourage teachers to provide research papers on value, they should participate in seminars and workshops to improve their teaching skills. Thus, when teachers combine with the subject during learning teaching and teach them values, students can become better citizens.